Epitaxy of obliquely aligned GaN nanorods on vertically oriented graphene nanosheets for transparent flexible piezoelectric nanogenerators. (April 2018) - Tsai, Shu-Ju; Wu, Chung-Lin; Tsai, Nien-Ting; Wong, Sheng-Shong; Tu, Li-Wei
Abstract: Transparent flexible piezoelectrics are important for a variety of applications, including piezoelectric transistors, nanogenerators, self-powered nano/biosensors, and piezo-phototronic effect enhanced solar cells and light-emitting diodes. Moreover, obliquely aligned nanorods (NRs) maximize NR deformation, enhancing the piezoelectric potential for applications involving piezoelectric, piezotronic, and piezo-phototronic effects. However, directly transferring one-dimensional semiconductor arrays onto transparent flexible substrates has been challenging. Herein, we report an efficient approach for growing and transferring a large area of obliquely aligned single-crystalline GaN NRs using vertically oriented graphene (VG) nanosheets. We demonstrated the high performance of transparent flexible vertically integrated nanogenerators (VINGs) embedded within the transferred obliquely aligned GaN NRs. The results indicated that nanocrystalline graphene was an excellent platform to epitaxy and transfer high-quality II-VI and III-V nanostructures for flexible, three-dimensional stacked electronics and to enhance the piezoelectric, piezotronic, and piezo-phototronic performance of piezoelectric nanostructure-based devices. Graphical abstract: Image